Caries OUT: COVID-19 adapted CCI multicenter study as an innovative cariology teaching ongoing experience. (2021)
Caries Care International (CCI) is a health outcomes focused, patient center, risk based caries management system (2019). UNICA with KCL and the University of leeds, designed a 1 year school children multicentre RTC to assess its caries-progression-control effectiveness. Twenty -one centre in 13 countries joined. AIM: this report aims and desrcribing the study s cariology related education strategies including pandemic-era adaptations. Methods: cariology education strategies: training center dentist in CCI througt the CCI Oral Health Record (OHR) an e-learning and a work shop. After the pandemic initiated, UNICA shifted to a multicentre single group children interventional study with pandemic adapted CCI (Non aerosol generating procedures, non AGP and remote consultation, plus a CCI short tooth brushing dietary habits behaviour change tool (SBCT) COM-B model